Food processing ([Chicago, Putman Pub. Co.], 1940)
Includes "Guide & Directory" issue.
Description based on: Vol.46, no.1(1985), title from vol. t. p.
Microfiche.
Summary in Arabic
Library has Also print format.
Keywords: Food industry and trade -- Periodicals; Food industry and trade -- Equipment and supplies -- Periodicals